Catalytic Asymmetric Synthesis of Alkynyl Aziridines: Both Enantiomers of cis‐Aziridines from One Enantiomer of the Catalyst. Issue 43 (9th September 2014) - Guan, Yong; López‐Alberca, Maria P.; Lu, Zhenjie; Zhang, Yu; Desai, Aman A.; Patwardhan, Aniruddha P.; Dai, Yijing; Vetticatt, Mathew J.; Wulff, William D.
Abstract Alkynyl aziridines can be obtained from the catalytic asymmetric aziridination (AZ reaction) of alkynyl imines with diazo compounds in high yields and high asymmetric inductions mediated by a chiral boroxinate or BOROX catalyst. In contrast to the AZ reaction with aryl‐ and alkyl‐substituted imines, alkynyl imines react to give cis‐substituted aziridines with both diazo esters and diazo acetamides. Remarkably, however, the two diazo compounds give different enantiomers of the cis‐aziridine from the same enantiomer of the catalyst. Theoretical considerations of the possible transition states for the enantiogenic step reveal that the switch in enantiomers results from a switch from Si‐face to Re‐face addition to the imine, which in turn is related to a switch from reaction with an E‐imine in the former and a Z‐isomer of the imine in the latter.